The Role of Social Culture in the Physical Performance of Volleyball Players in Jayapura Regency - Rif'iy Qomarrullah; Fredrik Sokoy (Universitas Negeri Semarang, 2024)
This research investigates how social and cultural factors influence the physical performance of volleyball athletes in this region, aiming to address the gap in knowledge regarding the athletes’ physical capabilities. This study focuses on a sample of young, elite male volleyball players in Jayapura Regency, examining how social and cultural elements shape their physical development and preparedness for competitive play. The primary objective is to assess the physical condition of these athletes and comprehend the cultural influences that contribute to their performance levels. This will provide valuable insights for improving training and development programs. A quantitative descriptive approach was employed, utilizing data collected through standardized physical performance tests. The sample comprised 37 male volleyball players, and the data were analyzed using descriptive statistics. Additionally, qualitative methods, including interviews and observations, were employed to gain a deeper understanding of the cultural context surrounding volleyball training. The physical tests revealed a range of performance levels among the athletes. Approximately 20% demonstrated a ‘very good’ performance, 24% showed ‘good’ performance, 29% exhibited ‘sufficient’ performance, while 14% had ‘unfavorable’ performance, and 13% displayed ‘very unfavorable’ performance. These results provide a snapshot of the volleyball players’ current physical condition and highlight key physical components such as speed, flexibility, strength, explosive power, agility, and endurance. The study underscores the significant role of social culture in shaping the physical performance of volleyball players in Jayapura Regency. Community support, traditional values, and communal training practices were identified as critical cultural factors influencing athletic development.